Socio-ecological Vulnerability of Smallholders due to Climate Change in Mountains: Agroforestry as an Adaptation Measure - Pandey Rajiv; Meena Dhanraj; Aretano Roberta; Satpathy Sachidananda; Semeraro Teodoro; Kumar Gupta Ajay; Rawat Sushma; Zurlini Giovanni (Change and Adaptation in Socio-Ecological Systems, 2015)
The present study aims to assess the socioecological vulnerability of smallholders through an index of Tehri Garhwal Himalaya. The index provides a realistic approach to recognize the contributions of social and ecological factors for household welfare vulnerability to climate change. The approach puts forward various indices for each component of vulnerability to climate change - exposure, sensitivity, and adaptive capacity including two more indices: one for overall impact under the exposure of climate change and another for overall vulnerability. The five indices were proposed to assess the vulnerability status of with and without agroforestry practicing households in Himalayan region. These indices are based on 35 indicators (8 for exposure; 12 for sensitivity, 15 for adaptive capacity), selected through inductive approaches. A questionnaire for households was designed for the above aim and was administered to 121 heads of households through face-toface interviews with 77 households practicing agroforestry and 44 without agroforestry. The questionnaire dealt the general household information, and indicators of the vulnerability including the issues related to agroforestry. The results highlight slightly higher adaptive capacity of agroforestry practicing households due to specific contribution of agroforestry. The low contribution of agroforestry among smallholders was due to small land holding. The study also results that remoteness, specific issues of smallholders’ such as poverty, education and employment are responsible for the present condition. In particular this study clearly shows that poverty is the key driver for vulnerability. All of these issues can be addressed if future programs and policies, include and implement regulations to remedy attributive factors. This paper may be applicable to other mountainous regions providing insights for effective adaptation strategies to climate change.